2022
DOI: 10.1177/15910199221097475
|View full text |Cite
|
Sign up to set email alerts
|

Application of convolutional network models in detection of intracranial aneurysms: A systematic review and meta-analysis

Abstract: Introduction Intracranial aneurysms have a high prevalence in human population. It also has a heavy burden of disease and high mortality rate in the case of rupture. Convolutional neural network(CNN) is a type of deep learning architecture which has been proven powerful to detect intracranial aneurysms. Methods Four databases were searched using artificial intelligence, intracranial aneurysms, and synonyms to find eligible studies. Articles which had applied CNN for detection of intracranial aneurisms were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Another recent systematic review and meta-analysis included 20 CNN studies to identify cerebral aneurysms. 77 Our systematic review emphasizes the current low level of evidence which undermines the performance accuracy of reported studies including those using CNNs, whereas the review by Abdollahifard et al does not raise any concerns regarding the bias or applicability of the studies. The discrepancy is potentially because we systematically applied PRISMA-DTA and QUADAS-2 methodology, which is the standard used for diagnostic accuracy studies.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Another recent systematic review and meta-analysis included 20 CNN studies to identify cerebral aneurysms. 77 Our systematic review emphasizes the current low level of evidence which undermines the performance accuracy of reported studies including those using CNNs, whereas the review by Abdollahifard et al does not raise any concerns regarding the bias or applicability of the studies. The discrepancy is potentially because we systematically applied PRISMA-DTA and QUADAS-2 methodology, which is the standard used for diagnostic accuracy studies.…”
Section: Discussionmentioning
confidence: 78%
“…Our systematic review and meta-analysis provide evidence for the quality and performance accuracy of all published studies using AI CAD for aneurysm detection. Another recent systematic review and meta-analysis included 20 CNN studies to identify cerebral aneurysms 77. Our systematic review emphasizes the current low level of evidence which undermines the performance accuracy of reported studies including those using CNNs, whereas the review by Abdollahifard et al does not raise any concerns regarding the bias or applicability of the studies.…”
Section: Discussionmentioning
confidence: 84%
“…To further highlight this conclusion, we can see that AI strengthens the performance of human operators such as radiologists in other fields such as screening of mammograms and breast cancer 44 45. The implications oare also observed to be highly appliable in neuroradiology since AI models have proven to improve the metrics of physicians when used as an assistant tool 15…”
Section: Discussionmentioning
confidence: 81%
“…This study demonstrated that the higher the size of the hematoma, the higher the detection rate is. Although DL is a black box, and the way it segments and detects lesions has not been well understood, similar articles have reported relatively similar results 1 5 26 …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation